Health surveillance and endocrine disruptors - William Waissmann
The author discusses the extreme relevance of research on the presence of endocrine disruptors (EDs) in products of interest to health surveillance (HS). Focusing on EDs, the author highlights the urgency of changes already under way in the direction of HS. The shift should be from product and product-registration approaches to the productive process and its realization in consumption, generation of contaminants, and alterations in the health of workers and the overall population. He briefly describes: regulatory gaps for dealing with EDs; difficulty in evaluating risk and suspension of the production and use of products with its characteristics and the need, as exemplified by such products, to enhance the inter-relationship among all stakeholders and to turn HS into a state-of-the-art technological setting, associated with the academic community and accountable to the public. The author reports on measures already taken in relation to EDs, including the establishment of a reference laboratory for analyzing persistent organic pollutants (POPs), interruption of the use of various POPs in Brazil and an initial review of requirements for registering pesticides under the Brazilian National Health Surveillance Agency (ANVISA).